The influence of temperature and electroforesis deposition green inhibitor on bipolar plate AA5052 in sulfuric acid medium - I Gusti Ayu Arwati,; Majlan, Edy Herianto; Loh, Kee Shyuan; Teuku Husaini,; Alva, Sagir; Muhajirin,; Nabilah Afiqah Mohd Radzuan, (Penerbit Universiti Kebangsaan Malaysia, 2020)
Aluminum alloy 5052 (AA5052) contains Mg (2.2-2.8.8% weight), Cu (0.1% weight), Cr (0.15% weight), Zn (0.1% weight), Si and Fe (0.45% weight) compositions. This material has been widely used as a bipolar plate in Proton exchange Membrane (PEMFC) fuel cells. This material has several advantages such as: lightness, high conductivity, good tensile strength, and flexibility. PEMFC operations produce several by-products, such as water and heat. Generally, the operation of PEMFC is around 333-353 K and the environment is acidic. In this condition the bipolar plate AA5052 will easily experience rust, thus lowering the performance of the PEMFC. In this study, 0.5 g/L Arabic Gum (AG) used as a green inhibitor and coated onto the AA5052 surface through electrophoretic deposition (EPD). The corrosion test was performed in 0.5 M H2 SO4 (pH 2) solution under the simulated PEMFC condition. Scanning electron microscopy (SEM) was used to analyze the morphology, and potentiodynamic polarization to determine the corrosion rate. Result shows that AG coating can reduce 60% the corrosion rate of AA5052 after immersed in 0.5 M H2 SO4 for 168 h. The effect of temperature on the inhibition efficiency reached 14.4% under the same condition. AG can be used as a green inhibitor to reduce the corrosion rate of AA5052 bipolar plate.